Yoga as Holistic Approach to Stress Management Across the Lifespan: Benefits for Children, Adults, and Seniors - Pankaja Pandey; Anulekha Dey; Kiran (Recent Trends in Sports, 2024)
Stress affects both mental and physical health and has become a commonplace aspect of life in today's fast-paced culture. This essay examines yoga's function as a comprehensive stress-reduction strategy, emphasizing methods that encourage calmness and strengthen resilience. By examining various research studies conducted on stress management through yoga. This study investigates their effectiveness in reducing stress and fostering emotional balance. Empirical evidence and psychological theories supporting the practice of yoga as a tool for stress relief are discussed. Additionally, this paper highlights the potential of yoga to enhance an individual's capacity for resilience, enabling better coping mechanisms in the face of stressors. Yoga's ability to reduce stress is said to depend on the incorporation of mind-body activities including meditation, asanas (physical postures), and pranayama (breathing methods). The study also looks at how regular yoga practice reduces stress and enhances general wellbeing, making it an important tool for long-term mental and emotional health. Additionally, because of its versatility, yoga can be practiced by people of varied ages, physical capabilities, and lifestyles. Yoga is incredibly helpful in preventing stress and maintaining general mental health because of its all-encompassing approach, which provides a long-lasting means of developing self-awareness, emotional regulation, and mindfulness.
Keywords: Emotional balance; Meditation; Mental health; Yoga; mindfulness; resilience